Oral Lumenoscopy: An Adjuvant in Early Screening of Oral Cancer - Anshul Aggarwal; Renuka Ammanagi; Vaishali Keluskar (Wolters Kluwer Medknow Publications, 2011)
The World Health Organization has strongly identified prevention and early detection as one of the major objectives in the control of oral cancer worldwide. Population-based mass screening of oral cancer appears to be a promising health promotion strategy with significant increase in survival rate- However, the current protocol comprising conventional visual inspection and palpation of oral soft tissues for the early detection of premalignant or malignant changes appears to be deficient. 1 Neoplastic epithelial cells tend to have an altered nuclearcytoplasmic ratio. Dehydration with acetic acid highlights this nuclear density and imparts an "acetowhite" appearance to tissue. This phenomenon can be further amplified by replacing conventional lighting with diffuse blue-white chemiluminescent illumination. This article aims to review the usefulness of this screening technology in early detection of oral cancer. The oral lumenoscopy has been proposed to be a method to improve oral screening methods which assist in the identification, evaluation and monitoring of oral mucosal changes. It is a simple, inexpensive and objective method that can provide real-time result for the detection of oral neoplasia which can be used in day to day practice by general dentist.